Say you love me - Simply Red; Warner Music (United Kingdom : Warner Music, 1998)
Contains the single track taken from the album Blue.
Say You Love Me.
Koleksi Khas Wiramanja.
AGM are Andy Wright, Gota Yashiki and Mick Hucknall.
Title from container.
Keywords: Songs, English; Popular music